2011
DOI: 10.1099/mic.0.046789-0
|View full text |Cite
|
Sign up to set email alerts
|

GapA+ Mycoplasma gallisepticum ts-11 has improved vaccine characteristics

Abstract: Mycoplasma gallisepticum (MG) is an important poultry pathogen that causes respiratory disease and loss of production worldwide, and is currently controlled with live attenuated vaccines. These vaccines have limitations as they vary in their pathogenicity, the protection afforded and their transmissibility, but have been shown to effectively reduce losses associated with challenge in the field. A live attenuated vaccine, ts-11, has been used for the control of M. gallisepticum in several countries. This vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…This insertion has been predicted to disrupt the protein and affect the adherence capability of M. gallisepticum, and consequently, this insertion in GapA affects the colonization of chickens by the vaccine strain (34). The insertional mutation was lost in the M.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This insertion has been predicted to disrupt the protein and affect the adherence capability of M. gallisepticum, and consequently, this insertion in GapA affects the colonization of chickens by the vaccine strain (34). The insertional mutation was lost in the M.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported reversion of GapA − to GapA + when ts-11 is passaged in chickens, resulting in an increased ability of the bacteria to colonize. However, GapA + ts-11 isolates are not pathogenic (18, 34), indicating that additional changes are necessary for full reversion to the virulent phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, complementation of R high with both gapA and crmA restored its cytadherence, its capacity to establish infection in the respiratory tract of chickens and its virulence (MudahiOrenstein et al, 2003;Papazisi et al, 2002). Previous studies have also shown that GapA is expressed at very low levels in the ts-11 vaccine strain and that variants of ts-11 that express GapA have enhanced capacity to establish infection and induce protective immunity (Mudahi-Orenstein et al, 2003;Shil et al, 2011). In our current study, Western blot analysis revealed that CrmA, but not GapA, was expressed in ST mutants 02-1 and 06-1, while ST mutant 33-1 did not express CrmA.…”
Section: Discussionmentioning
confidence: 99%
“…While scoring of tracheal mucosal lesions has been used to assess mycoplasmosis in chickens (Nunoya et al, 1987;Shil et al, 2011), the present study and that of Sanei et al (2007) appear to be the first to describe the use of tracheal mucosal lesion scoring to assess changes seen after M. gallisepticum infection in turkeys. The lesions seen in our study were generally mild to moderate (scores of 1 to 2), except in birds exposed to the highest dose of Ap3AS, most of which had severe lesions (score 3).…”
Section: Discussionmentioning
confidence: 99%
“…Such a model has not been developed for turkeys. Furthermore, while the histology of the lesions induced by M. gallisepticum in chickens in the trachea and air sacs has been described (Nunoya et al, 1987;Shil et al, 2011), the histopathology of the tracheal mucosa, air sacs and infraorbital sinuses of turkeys after infection with M. gallisepticum has not been fully explored, and neither have quantitative methods for assessing the severity of disease been fully described for turkeys.…”
Section: Introductionmentioning
confidence: 99%